Lived Experiences of English Teachers in Enhancing Learners’ Confidence and Engagement in Language Learning - Diana Jane Reyes; Jeffrey Astillero (International Journal on Integrated Education, 2026)
Effective communication skills play a vital role in facilitating meaningful interaction, promoting understanding, and enhancing engagement in learning contexts. Despite the importance of English proficiency in academic and professional success, many Filipino learners continue to experience challenges in oral communication due to linguistic and affective barriers. This study explored the lived experiences of English teachers in enhancing learners’ confidence and engagement in English language learning and examined the strategies used to address these challenges. A qualitative phenomenological research design was employed, involving ten junior high school English teachers selected through purposive sampling. Data were gathered through in-depth interviews and analyzed using Colaizzi’s method. Findings revealed that teachers foster learner confidence through inclusive and supportive practices, including first-language support, positive reinforcement, collaborative activities, and the establishment of a safe classroom environment. Learners, however, experienced linguistic difficulties such as limited vocabulary and weak grammar, as well as affective barriers such as fear of mistakes and language anxiety. Teachers addressed these challenges through scaffolded instruction, interactive activities, constructive feedback, and psychologically safe learning environments. The study highlights the importance of supportive classroom practices in enhancing learner confidence and engagement and resulted in the development of a practical primer for English teachers.